Procedure for Supervision of Apron Movement Control Unit (AMC) for Service Users in Sultan Mahmud Badarudin II International Airport, South Sumatra - Marsinah Marsinah; Fitria Marisya; Hatidah Hatidah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to ascertain how service users are supervised by the Apron Movement Control Unit and how service users are dissipated by the Apron Movement Control Unit at Sultan Mahmud Badarudin II International Airport in South Sumatra. This study employs primary and secondary data in a qualitative manner. Three methods of gathering data were employed: documentation, interviews, and observation. The study's findings support the assertion that the AMC unit oversees all tarmac operational activities related to the discipline of service users, including monitoring the speed of GSE and officer vehicles, regulating passenger and person mobility, supervising the use of equipment that agents are required to use, such as safety vests, supervising engine travel, supervising refuelling, and keeping an eye on the apron area's cleanliness. The AMC unit monitors everyone's movement, including passengers, and imposes discipline on service users on the air side (apron). Ground handling agents who violate the guidelines face disciplinary action from the AMC. The person in question receives a straight reprimand, and if they receive one of these actions three times in a row, their airport pass is cancelled or withheld, making it impossible for them to work on the airside or apron areas.